MAPK4 Accelerates Progression of Cervical Squamous Cell Carcinoma by Positively Regulating SLC3A2 Expression - Jing YU; Lu DENG; Yuting ZHAO; Zhenlong YUAN; Lingying WU (Zhongliu Fangzhi Yanjiu)
ObjectiveTo explore the role of MAPK4 in cervical squamous cell carcinoma (CSCC) for the identification of candidate prognostic prediction biomarkers and molecular therapeutic targets. MethodsThe TCGA cohort was subjected to Kaplan-Meier survival analysis. Immunohistochemistry experiments were conducted on clinical samples to explore the correlation between MAPK4 and patient prognosis. A nomogram was constructed based on MAPK4 mRNA levels. Western blot, CCK-8, colony formation, and Transwell cell function experiments were performed to clarify the abnormal expression and role of MAPK4 in CSCC. DIA proteome sequencing was used to identify effector molecules regulated by MAPK4. Combined with the above cell function experiments, the knockdown of MAPK4 and the overexpression of effector molecules revealed that MAPK4 regulated effector molecules to mediate tumor progression. ResultsCSCC patients with elevated MAPK4 mRNA levels and high protein expression have a worse prognosis. The constructed nomogram based on MAPK4 can accurately predict the 1-, 3-, and 5-year survival rates of patients. Compared with that in normal cervical tissues, MAPK4 protein expression was up-regulated in tumors. MAPK4 knockdown substantially inhibited the proliferation, colony formation, migration, and invasion of CSCC ME180 and SiHa cells. SLC3A2 is a downstream effector molecule of MAPK4. Overexpression SLC3A2 can weaken the inhibitory effect of MAPK4 knockdown on cell proliferation, colony formation, migration, and invasion. ConclusionMAPK4 is a candidate prognostic biomarker for patients with CSCC. MAPK4 positively regulates SLC3A2 protein expression and accelerates tumor progression, making it a potential molecular therapeutic target for patients with CSCC.